2020
DOI: 10.1152/ajpendo.00344.2019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acute and short-term dietary fat ingestion on postprandial skeletal muscle protein synthesis rates in middle-aged, overweight, and obese men

Abstract: Muscle anabolic resistance to dietary protein is associated with obesity and insulin resistance. However, the contribution of excess consumption of fat to anabolic resistance is not well studied. The aim of these studies was to test the hypothesis that acute and short-term dietary fat overload will impair the skeletal muscle protein synthetic response to dietary protein ingestion. Eight overweight/obese men [46.4 ± 1.4 yr, body mass index (BMI) 32.3 ± 5.4 kg/m2] participated in the acute feeding study, which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 48 publications
2
21
1
Order By: Relevance
“…Furthermore, both obesity and low muscle mass may be associated with anabolic resistance—the limited skeletal muscle protein synthetic response after an anabolic stimulus, for example, protein intake or physical activity ( 33 38 ). Nevertheless, how this mechanism works remains to be elucidated as recent studies did not find an association of obesity or fat intake on muscle protein synthesis ( 39 , 40 ).…”
Section: The Interplay Between Obesity and Sarcopenia In Old Agementioning
confidence: 99%
“…Furthermore, both obesity and low muscle mass may be associated with anabolic resistance—the limited skeletal muscle protein synthetic response after an anabolic stimulus, for example, protein intake or physical activity ( 33 38 ). Nevertheless, how this mechanism works remains to be elucidated as recent studies did not find an association of obesity or fat intake on muscle protein synthesis ( 39 , 40 ).…”
Section: The Interplay Between Obesity and Sarcopenia In Old Agementioning
confidence: 99%
“…Glucose is the main energy staple of our diet, and we base on 3C substrates most of our metabolic function and regulation [ 36 , 47 , 48 ]. Instead, we centered our attention on lipid (2C sources) [ 285 , 286 , 287 ], sugars as such [ 288 ], some minerals (e.g., salt), and, to a limited extent, on protein [ 289 ]. It is unclear why our flag substrate, glucose, has not been given due importance except as a marker of disease.…”
Section: Diet Its Composition and The Central Role Of Glucosementioning
confidence: 99%
“…There is accumulating evidence that obesity, which represents another model of lipid overload, suppresses the stimulation of MPS rates following dietary protein ingestion (144,145) , combined feeding and resistance exercise (148) in human subjects. A recent study was the first to investigate the impact of high fat feeding on MPS in human subjects (149) . This study reported that, in overweight and obese middle-aged men, neither the acute consumption of a high fat meal nor 2 weeks of overfeeding via a high-SFA diet had a detrimental effect on the MPS response to dietary protein ingestion.…”
Section: ‘Lipid Saturation’: Lipid-derived Adipose Signals and Skeletmentioning
confidence: 99%
“…This suggests that IR may be necessary to produce lipid overload-induced AR in human subjects. It will be interesting for future studies to investigate whether longer-term high fat feeding interventions that result in IR also lead to the development of AR (149) .…”
Section: ‘Lipid Saturation’: Lipid-derived Adipose Signals and Skeletmentioning
confidence: 99%